What distinguishes potential entrepreneurs from people who not want to be entrepreneurs? - Gaspar, Fernando (2010)
Entrepreneurship has become an important subject for academics and for politicians all over the western world. Particularly for countries in the euro zone, whose ability to use demand side politics has been severely shortened, the need to improve economic growth through the stimulation of the aggregate supply is one of the priorities of these days. It is a reasonable assumption that increasing entrepreneurship is an important objective. The thing is HOW. What can governments do to increase the creation of new companies? A large number of studies have been published on this subject, many of them trying to contribute for answers to this question, and most of them studying successful entrepreneurs. That means most studies look at people who, not only decided to create their own companies but also succeeded at that activity. Most studies don’t look at people who created their own companies but failed. Rare studies look at people who decided not to become entrepreneurs. Following studies about entrepreneurial intentions this communication takes the data from such a study and tries to identify differences between a) people who say they want to be entrepreneurs and b) people who clearly say they do not want to create their own organization. So this communication looks at people who flat out say, at an early age (university final year students), they don’t want to be entrepreneurs. It tries to identify what distinguishes these people from the ones who want to be entrepreneurs and it tries to answer the question: why? Why don’t they want to become entrepreneurs? Are they concerned they will not be successful? Do they believe they will not be able to assemble the necessary resources? Are they unable to identify entrepreneurial opportunities? Do they think society values the entrepreneur’s role? Conclusions are drawn, based on this sample, concerning what governments, universities and other interface structures can do to change these people’s ideas about entrepreneurship.